Efficacy of cooling therapy and α‐lipoic acid derivative against chemotherapy‐induced alopecia in an animal model. Issue 3 (15th November 2022) - Aiba, Takayuki; Kono, Yohei; Etoh, Tsuyoshi; Kawano, Yoko; Oshima, Yusuke; Inomata, Masafumi
Abstract: Chemotherapy‐induced alopecia is frequently induced by various regimens of chemotherapy and has a significant impact on mental health and quality of life. However, the effect of available current treatment for chemotherapy‐induced alopecia is not sufficient. This study aimed to clarify the therapeutic effects and mechanism of skin cooling and the antioxidant α‐lipoic acid derivative on chemotherapy‐induced alopecia. We developed a chemotherapy‐induced alopecia model of cyclophosphamide (120 μg/g) using Institute of Cancer Research mice. We used cooling therapy and α‐lipoic acid derivative application as the treatments. We compared the alopecia score, hair bulb diameter, insulin‐like growth factor‐1 level, vascular permeability, and apoptosis between the control and treatment groups. The alopecia score significantly improved in each treatment group compared with that in the cyclophosphamide group. Hair bulb diameter significantly improved in the cyclophosphamide + cooling group compared with that in the cyclophosphamide group. The insulin‐like growth factor‐1 level and vascular permeability level was significantly retained and suppressed, respectively, in each treatment group compared with that in the cyclophosphamide group. The number of apoptotic cells in the vascular endothelium significantly decreased in the cyclophosphamide + α‐lipoic acid derivative group compared with that in the cyclophosphamide group. In conclusion, cooling therapy and α‐lipoic acid derivative facilitated recovery from chemotherapy‐induced alopecia caused by cyclophosphamide through decreasing vascular permeability. Abstract : Chemotherapy‐induced alopecia is frequently induced by various regimens of chemotherapy and has a significant impact on mental health and quality of life. In this study, we demonstrated that cooling therapy and a‐lipoic acid derivative facilitated recovery from chemotherapy‐induced alopecia caused by cyclophosphamide through decreasing vascular permeability.